DESIGN AND BUILD OF PULSE BALANCE DEPOSIT INFORMATION SYSTEM BASED ON WEBSITE AT PT ASIA ADIJAYA PERKASA - Softi Ulin Nuha; Agustina Srirahayu; Eko Purwanto; Ajeng Putri Sulistyawati (Proceeding of International Conference on Science, Health, And Technology, 2022)
The credit balance deposit business is said to be still loved until now, the need for all-in-one online makes it inevitable that device users need to top up pulses, digital wallets, PLN or top up games. This makes transaction requests more and more causing many requests in the deposit process, with this problem the author wants to create a credit deposit information system. In this study, the method used by the researcher divides it into two, namely for the first method of data collection there are observations, interviews, literature studies, and documentation. The second is the system development method using the SDLC (Systems Development Life Cycle) method, there is a needs analysis using pieces analysis, where there are system workflows, use case diagrams, activity diagrams, Sequence diagrams and the last is testing using black box techniques and beta testing. The results of the recommendation system consist of three access rights, namely customer service, owner and member. The credit balance deposit information system can assist in the deposit process from transactions, data presentation and reporting. The results of the black box test show that all functions in the credit balance deposit information system can run as expected. The results of beta testing by filling out the questionnaire show the percentage value of the system suitability is 88.79%.